Microbiological Evaluation of Chicken Carcasses in an Immersion Chilling System with Water Renewal at 8 and 16 Hours - Souza, Luiz Carlos de [UNESP]; Pereira, J. G. [UNESP]; Spina, T. L. B. [UNESP]; Izidoro, T. B. [UNESP]; Oliveira, A. C.; Pinto, José Paes de Almeida Nogueira [UNESP] (Int Assoc Food Protection, 2012)
Since 2004, Brazil has been the leading exporter of chicken. Because of the importance of this sector in the Brazilian economy, food safety must be ensured by control and monitoring of the production stages susceptible to contamination, such as the chilling process. The goal of this study was to evaluate changes in microbial levels on chicken carcasses and in chilling water after immersion in a chilling system for 8 and 16 h during commercial processing. An objective of the study was to encourage discussion regarding the Brazilian Ministry of Agriculture Livestock and Food Supply regulation that requires chicken processors to completely empty, clean, and disinfect each tank of the chilling system after every 8-h shift. Before and after immersion carcasses were collected and analyzed for mesophilic bacteria, Enterobacteriaceae, conforms, and Escherichia coli. Samples of water from the chilling system were also analyzed for residual free chlorine. The results do not support required emptying of the chiller tank after 8 h; these tanks could be emptied after 16 h. The results for all carcasses tested at the 8- and 16-h time points indicated no significant differences in the microbiological indicators evaluated. These data provide both technical and scientific support for discussing changes in federal law regarding the management of immersion chilling water systems used as part of the poultry processing line.